Cultura de embrião zigótico, calogênise e conservação in vitro de Erythrina velutina Willd. (Leguminosae) - Fonseca, Priscila Tavares (2012)
Erythrina velutina is a native Caatinga biome, with increasing socio-economic importance and medical. The objective of this work were to culture zygotic embryo, as well as in vitro E. velutina callus formation and conservation. The first experiment was a comparative study of seed germination between intact and embryo rescue evaluating the effect of plant growth regulators BAP and NAA on in vitro morphogenesis. The second experiment was verify the effect of BAP and CIN in the nodal segments regeneration. The third experiment observed the effect of 2,4-D on in vitro callus formation from different explants: zygotic embryos whole and sectioned, leaves and epicotyl. In callus cultures of zygotic embryos we analyzed the kinetics growth, quantified if the AR and AST did to plant anatomy. In the last experiment evaluated the effect of sucrose osmotic agent and the PBZ growth retardant the in vitro conservation. For germination of zygotic embryos cultivation provided more vigorous plants. The plumule explant and zygotic embryos can be regenerated at concentration of 4.0μM of BAP, the intermediate regions and the radicle promoted formation of compact callus on the combination of 10.63μM BAP and 2.0μM NAA. In regeneration in vitro concentration of 21.03μM BAP induced higher number of shoots in nodal segments. For callus formation concentration of 10.65μM 2,4-D induced friable callus on zygotic embryos whole and the reduction of AR, AST and the presence of dividing cells and amyloplasts during the growing period. The growth curve showed that callus should be transferred to subculture medium between the 15th to the 21st day. In the tested concentration of 11.75μM 2,4-D was obtained friable callus on leaf segments. We observed slower cultures growth at a temperature of 18°C, concentrations of up to 175.28mM sucrose was not sufficient to reduce plant growth. When using PBZ was observed a reduction of plant growth when added to the culture medium 4μM of BPZ.